42nd AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2006
DOI: 10.2514/6.2006-5010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Electrospray Plume from the EMI-Im Propellant Externally Wetted on a Tungsten Needle

Abstract: Public reporting burden for this collection of information is estimated to average I hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducng this burden to Department of Defense, Washington Headquarters Services, Directorate for Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The elevated baseline reading between ±15°, which has been observed previously in needle mass spectra, is attributed to large m/q species that are not completely filtered out by the mass filter and reach the detector. 22,23 It is possible to use the intensity trend of each species to approximate the location of origin of that species in the Taylor cone. Maximum n = 0 cation intensities are observed at high angle values.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated baseline reading between ±15°, which has been observed previously in needle mass spectra, is attributed to large m/q species that are not completely filtered out by the mass filter and reach the detector. 22,23 It is possible to use the intensity trend of each species to approximate the location of origin of that species in the Taylor cone. Maximum n = 0 cation intensities are observed at high angle values.…”
Section: Resultsmentioning
confidence: 99%
“…At lower field strengths, a range of cluster sizes can be produced. This is observed in the molecular-beam/mass-spectrometry measurements of Chiu et al [14], as described in the Introduction. …”
Section: Discussionmentioning
confidence: 66%
“…In recent work, Chiu et al [14] used molecular beam/mass spectrometry to analyze the plume of an electrospray with 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMI-Im) † as the propellant. They showed that for the operating conditions imposed, at least two positive ion cluster sizes and a background that is likely fragmented droplets are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Also, since most metals have very high melting points, the choice of propellant is limited to a few low melting metals and alloys. For these reasons, in recent years, ionic liquids have been described as ideal propellants for electrospray thrusters due to their negligible vapor pressures, high electrical conductivities, low melting temperatures, and wide liquid temperature range . Furthermore, because the physical properties can be tuned, key properties affecting the hydrodynamics, such as viscosity and surface tension, can be also optimized for this application.…”
Section: Space Propulsionmentioning
confidence: 99%
“…Although, in this particular study, the specific impulse ( I sp = 292 s, for a mass flow rate m · = 2.1 × 10 −10 kg s −1 and an acceleration voltage V A = 5000 V) was found to be too low to be considered in electrospray thrusters, the authors indicated their expectation that, with future optimization in terms of the choice of IL and operating conditions, ionic liquids should prove to be excellent electrospray propellants. [C 2 mim][NTf 2 ] was later investigated by NASA for the Space Technology 7 – Disturbance Reduction System Mission (ST7‐DRS) and passed the space environment tests .…”
Section: Space Propulsionmentioning
confidence: 99%